Advancements in the Exploration of Gel Electrolytes for Aqueous Zinc Ion Batteries - Yi Xiong; Jinhang Dai; Lingyao Kuang; Xiaodan Li; Xingxing Gu (Bulletin of Chemical Reaction Engineering & Catalysis, 2023)
Aqueous zinc-ion batteries (ZIBs) are seen as a superior substitute for lithium-ion batteries (LIBs) due to their excellent safety, low cost, and eco-friendliness. However, problems such as zinc dendrite growth, hydrogen evolution reaction and electrode corrosion hinder the commercialization of batteries. Electrolyte as a link to other parts of the battery, has been widely concerned. Hydrogel is a kind of cross-linked product filled with water, which has the advantages of high theoretical capacity, good flexibility, good water retention and good mechanical properties, and becomes a potential candidate for ZIBs. By summarizing the development of hydrogel electrolytes, the cross-linking types of gel electrolytes and their applications in ZIBs were reviewed in this paper. Finally, the application of gel electrolyte in ZIBs is summarized and prospected, which brings a meaningful reference for the development of ZIBs. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).